Acute and Post-traumatic Stress Disorder Symptoms in Mothers and Fathers Following Childbirth: A Prospective Cohort Study - Schobinger, Elisabeth; Stuijfzand, Suzannah; Horsch, Antje (Frontiers in Psychiatry, 2020)
Introduction: Up to 30% of women view their childbirth as traumatic. This experience can lead to acute stress disorder or posttraumatic stress disorder. The negative impact of maternal posttraumatic stress disorder following childbirth reaches beyond the mother, affecting her child’s development and the couple’s relationship. Research on paternal posttraumatic stress disorder following childbirth is scarce. Acute stress disorder is suggested to be an important predictor of posttraumatic stress disorder in mothers, but little is known about paternal acute stress disorder following childbirth. Furthermore, there is limited information about the comparison or relation of acute stress disorder and posttraumatic stress disorder following childbirth between parents. Aim: (1) To compare the prevalence rates and severity of acute stress disorder and posttraumatic stress disorder symptoms between parents following childbirth by taking anxiety and depression symptoms, as well as obstetric variables and previous traumatic events into account and (2) To determine if acute stress disorder is a predictor of posttraumatic stress disorder. Method: A prospective population-based design was used. N = 647 participants were recruited from future parents who attended appointments at the Obstetrics and Gynecology unit at a Swiss university hospital. Self-report questionnaires were used: Posttraumatic Diagnostic Scale in the third trimester of pregnancy (T1) and one month postpartum (T3), Acute Stress Disorder Scale at one week postpartum (T2), and Hospital Anxiety and Depression Scale at all time points. Obstetric and neonatal variables were retrieved from hospital records. Results: At T2, 63.9% of mothers and 51.7% of fathers presented symptoms of acute stress disorder. At T3, 20.7% of mothers and 7.2% of fathers had symptoms of posttraumatic stress disorder. Acute stress disorder was a predictor of postpartum posttraumatic stress disorder (Odds ratio: 8.6). Depression symptoms was a significant confounder in the prediction of posttraumatic stress disorder following childbirth, but not anxiety or the previous loss of a baby.